Factors affecting issues on akhlak among undergraduates: a case of public universities - Mat, Zawiah; Che Husain, Faridah; Sulaiman, Mashitah (UTHM Publisher, 2022)
Development of human through the formation of akhlak among undergraduates play an important role in the life and civilization of a nation. The emphasis on akhlak aspects in higher education is essential to produce graduates with a balance between needs of duniawi and ukhrawi. Teaching and learning that focus on academic achievement alone is not enough to be relied upon in producing holistic graduates with knowledge, identity and practice good manners. This paper aims to identify the factors of moral degradation among students in the selected Public Universities. This study is based on quantitative methods by distributing questionnaires. A total of 1110 questionnaires were distributed randomly in four universities which are representing by zone. The northern zone is represented by Universiti Utara Malaysia (UUM), the east zone by Universiti Malaysia Terengganu (UMT), central zone by the University of Malaya (UM) and the south zone by Universiti Teknologi Malaysia (UTM). The findings show that the environment is becoming a major factor that encourages students to engage with moral problems